Webinar: Climate-Smart Agriculture Tools for Africa 13 October 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
To support a transition to Climate-Smart Agriculture in Africa, researchers and development practitioners have developed a range of tools and options for effective climate adaptation and mitigation in agriculture in different environments and at diverse scales. The Climate and Agriculture Network for Africa (CANA) together with CGIAR and development partners (CARE International Adaptation Learning program) bring you a webinar on CSA tools for Africa. We present five of these tools, providing an opportunity for participants to learn about them, thereby, allowing for integration of their use across scales. For any questions, write to cana@cgiar.org.